Indonesian Economic Recovery after COVID-19 Pandemic: Qur'anic Paradigm in Community Economic Development - M. Fauzan Zenrif; M. Lutfi Mustofa (Future Science)
My academic concern is that so far, some studies tend to look at economic recovery, during the COVID-19 period, focusing on planning, economic and social, economic and health, economic and political, economic and distribution, economic and monetary transmission. No researcher focused on the problems: how is the performance of the individual approach used by the government in solving economic problems? What constraints are experienced in problem-solving? and how is the community approach of the Quran as a solution to the economic recovery model? By using participatory action qualitative research and content analysis of the Quranic text, the result shows that community-based, using the qur’anic paradigm, can be a monetary recovery system based on religious, social spirit. This, at the same time, confirms the significance of the community-based development approach, combined with the values of the Qur'an, in solving community economic problems, due to the COVID-19 pandemic. The findings of the study term the pattern of economic recovery with the community approach have advantages, compared to the individual approach used by the government. The study also finds that the community's policy in economic recovery opens up more opportunities for the financial independence of the community. By using the community Passing-Loos Management System (CP-LMS), the concept of the Qur'an charity values, as the basis of the religious majority of Indonesian society, the community-based approach can be the foundation of Pancasila's economic development. Thus, the results of this study indicate that the pattern of integration, between the values of the Qur'an and the Pancasila economic system, as the SDGs authorized, can present an independent community economic system.